Biphenyl-induced cytotoxicity is mediated by an increase in intracellular Zn2+. (4th July 2019) - Ae, Masamichi; Imura, Naohiro; Inubushi, Tomoko; Abe, Shin; Yusuke, Bekki; Sugimoto, Mayumi; Kamemura, Norio
Abstract: Biphenyl is found both in natural and anthropogenic sources and is used as a fungistat in the packaging of citrus fruits. Acute exposure to high levels of biphenyl has been observed to cause skin irritation and toxic effects on the liver and kidneys. However, the mechanisms of cytotoxicity induced by biphenyl are not yet well understood. In the present study, the cytotoxicity of biphenyl was studied by flow cytometry with fluorescent probes. Biphenyl at 100 μM significantly increased cell lethality after 3 h in rat thymocytes. In addition, biphenyl at 100 μM or more elevated intracellular Zn 2+ levels. N, N, N′, N′-Tetrakis(2-pyridylmethyl)ethylenediamine (TPEN), an intracellular and extracellular Zn 2+ chelator, but not diethylenetriamine-N, N, N′, N″, N″-pentaacetic acid (DTPA), a membrane-impermeable Zn 2+ chelator, attenuated the biphenyl-induced increase in intracellular Zn 2+ levels and cell death. These results suggested that biphenyl-induced cytotoxicity caused an increase in intracellular Zn 2+ levels, which was dependent on internal Zn 2+ . Moreover, biphenyl led to an increase in sensitivity to oxidative stress, while TPEN inhibited this biphenyl-induced increase. Our findings revealed that biphenyl caused an increase in the intracellular free Zn 2+ concentration, inducing cytotoxicity, cell death, and an increase in sensitivity to oxidative stress.